A core rigidity classifier method and a novel approach to account for geometric effects on the elastic properties of sandwich structures. (15th February 2022) - da Silva, Rodrigo José; dos Santos, Júlio Cesar; Freire, Rodrigo Teixeira Santos; Batista, Fabiano Bianchini; Panzera, Túlio Hallak; Christoforo, André Luis; Scarpa, Fabrizio
Highlights: Sandwich panels can be interpreted as homogenised structures. The flexural modulus can be obtained by considering the homogenisation concept. Specimen dimensions influence the measured flexural modulus. Small specimens return underestimated values ​​for flexural modulus. Core rigidity influences bending behaviour. Abstract: Sandwich structures for engineering load-bearing applications are commonly characterised using three-point (3P) bending tests. Classical beam theory shows that the ratio between the flexural stiffness and moment of inertia of the cross-section (flexural modulus) in rectangular sandwich panels is independent of the support span length and width. Practice, however, indicates the opposite. The ASTM D7250 3P standard implicitly addresses this concept, as it recommends that the flexural and shear stiffness be determined in tests involving two different support span lengths. Nevertheless, the standard does not address the physical aspects related to the dimensions of the specimen (span length and panel width relative to panel thickness) on the elastic properties measured by using the 3P bending approach. The standard neither considers instances in which the sandwich core has a significant rigidity and the concept of sandwich flexural modulus. Such limitations impede the proper use of the standard in sandwich structures made from modern advanced materials with high rigidity and low-density cores. This work describes a novel approach to identify the geometric effects and proposes a criterion for the qualitative and quantitative classification of the core rigidity, called the RJS Method. The method allows characterising the sandwich flexural modulus under a single loading configuration in structures with a core of significant rigidity, showing that the closer the values of the global flexural modulus of the faces and core, and the smaller the thickness of the faces relative to panel thickness, the greater the core rigidity relevance.